Entering multiculturalism : Finnish experience abroad : papers from FinnForum VI - Koivukangas, Olavi (Siirtolaisuusinstituutti, 2002)
The first FinnForum was organized in 1974 in Duluth Minnesota and the sixth in Jyväskylä, Finland, in 2001. Numerous scholars from Finland, the United States, Canada and other countries have participated in the conferences and delivered papers on different topics related to Finnish migration movements and ethnicity. The theme af the VI FinnForum was Finland entering multiculturalism. ln the 1990's Finland turned from a land of emigration into a country of immigration with nearly 100 000 foreign citizens. The focus of the conference was how the Finnish experience abroad could help the present-day Finland in its efforts to become a multicultural and multilingual society. The VI FinnForum was organized by the Institute of Migration, Turku, and the University of Jyväskylä. Opening of the Conference / Olavi Koivukangas Multiculturalism – a global perspective / Tara Mukherjee Migration, citizenship & democracy in the EU / John Parry The need for multicultural approach in Finland / Olavi Koivukangas Preserving a vanishing legacy: Finnish American architecture and the National Register of Historic Places in the Upper Midwest / Arnold R. Alanen Romancing the tree / Wilbert David Bohm Roots and wings. Re-writing identity, tradition and culture: the shifting notion of self and community / Taina Chahal & Katja Mäki The ideological and cultural roots ofKarelian Fever in the Westem Lake Superior region / Richard Hudelson Speaking Finnish in Austria. Language attitudes among Finnish migrant women / Katja Jääskeläinen Finnish language outside Finland: a book project / Hannele Jönsson-Korhola Kaarlo Tuomi: man without a country - the tale of a Finnish American Russian spy / Michael G. Karni Is today's multiculturalism too late för Australian Finnish? / Magdolna Kovacs Finnish culture: utilizing ethnic identity in strategic development / Jim Kurtti Australian Finns and their language / Tiina Lammervo Ethnicity of K ven immigrants from North Norway in American society: two case studies / May Lunde Internet supporting the ...